Dexrazoxane and Long-Term Heart Function in Survivors of Childhood Cancer. Issue 12 (20th April 2023) - Chow, Eric J.; Aggarwal, Sanjeev; Doody, David R.; Aplenc, Richard; Armenian, Saro H.; Baker, K. Scott; Bhatia, Smita; Blythe, Nancy; Colan, Steven D.; Constine, Louis S.; Freyer, David R.; Kopp, Lisa M.; et al.
Abstract : PURPOSE: For survivors of childhood cancer treated with doxorubicin, dexrazoxane is cardioprotective for at least 5 years. However, longer-term data are lacking. METHODS: Within the Children's Oncology Group and the Dana Farber Cancer Institute's Childhood Acute Lymphoblastic Leukemia Consortium, we evaluated four randomized trials of children with acute lymphoblastic leukemia or Hodgkin lymphoma, who received doxorubicin with or without dexrazoxane, and a nonrandomized trial of patients with osteosarcoma who all received doxorubicin with dexrazoxane. Cumulative doxorubicin doses ranged from 100 to 600 mg/m 2 across these five trials, and dexrazoxane was administered uniformly (10:1 mg/m 2 ratio) as an intravenous bolus before doxorubicin. Cardiac function was prospectively assessed in survivors from these trials, plus a matched group of survivors of osteosarcoma treated with doxorubicin without dexrazoxane. Two-dimensional echocardiograms and blood biomarkers were analyzed centrally in blinded fashion. Multivariate analyses adjusted for demographic characteristics, cumulative doxorubicin dose, and chest radiotherapy determined the differences and associations by dexrazoxane status. RESULTS: From 49 participating institutions, 195 participants were assessed at 18.1 ± 2.7 years since cancer diagnosis (51% dexrazoxane-exposed; cumulative doxorubicin dose 297 ± 91 mg/m 2 ). Dexrazoxane administration was associated with superior left ventricular fractional shortening (absolute difference, +1.4% [95% CI, 0.3 to 2.5]) and ejection fraction (absolute difference, +1.6% [95% CI, 0.0 to 3.2]), and lower myocardial stress per B-type natriuretic peptide (–6.7 pg/mL [95% CI, –10.6 to –2.8]). Dexrazoxane was associated with a reduced risk of having lower left ventricular function (fractional shortening < 30% or ejection fraction < 50%; odds ratio, 0.24 [95% CI, 0.07 to 0.81]). This protective association was primarily seen in those treated with cumulative doxorubicin doses ≥ 250 mg/m 2 . CONCLUSION: Among young adult-aged survivors of childhood cancer, dexrazoxane was associated with a cardioprotective effect nearly 20 years after initial anthracycline exposure.